2015
DOI: 10.4028/www.scientific.net/msf.825-826.655
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of Mold Flow Simulations with Two-Scale Structural Mechanical Simulations for Long Fiber Reinforced Thermoplastics

Abstract: The entire simulation process for long fiber reinforced thermoplastics is examined to determine the effective mechanical properties which are influenced by the microstructural fiber orientation state. Therefore, flow and fiber orientation simulations are conducted and the obtained fiber orientation tensors are used in two-scale structural simulations. The fiber orientation distributions as well as the mechanical properties are compared with micro-computed tomography data and results from threepoint bending tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…This method enables the construction of 3D fibre orientation based on the 2D fibre crosssections. With the advancement of X-ray scanning technology and the development of powerful image processing and computing capabilities, 3D micro-computerised tomography (Micro-CT) has recently become a common technique for characterising the FOD and FLD in LFTs [197][198][199][200][201][202][203][204][205][206]. It is able to scan an LFT sample and generate 2D images, from which a 3D image is constructed.…”
Section: Fibre Content Fod and Fldmentioning
confidence: 99%
“…This method enables the construction of 3D fibre orientation based on the 2D fibre crosssections. With the advancement of X-ray scanning technology and the development of powerful image processing and computing capabilities, 3D micro-computerised tomography (Micro-CT) has recently become a common technique for characterising the FOD and FLD in LFTs [197][198][199][200][201][202][203][204][205][206]. It is able to scan an LFT sample and generate 2D images, from which a 3D image is constructed.…”
Section: Fibre Content Fod and Fldmentioning
confidence: 99%
“…Model ten w swoim założeniu opiera się na redukcji prędkości wzrostu wartości własnych tensora orientacji włókien przez współczynniki skalarne, nie zmieniając wartości wektorów obrotu. W odniesieniu do modelu Folgara-Tuckera został on zapisany w następującej postaci [14][15][16][17]: 3We wspomnianym modelu, w porównaniu z klasycznym modelem Folgara--Tuckera, parametr dyfuzyjny jest zredukowany o współczynnik skalarny κ, natomiast tensor czwartego rzędu aijkl jest zastąpiony wyrażeniem: Model RSC może być użyty do uchwycenia powolnej dynamiki orientacji włókien, gdy współczynnik skalarny κ <= 1. Im mniejsza jest wartość współczynnika skalarnego, tym wolniej wartość tensora orientacji zmienia się wraz z przepływem tworzywa i powstaje grubsza warstwa rdzenia.…”
Section: Wprowadzenieunclassified
“…Such a coupling has already been considered in short-fiber thermoplastic injection molding with a validation using a demonstrator and is also available for commercial use [15]. For the compression molding process of long-fiber-reinforced thermoplastics, Buck et al [16] showed the effect of coupling process and structure simulation. Görthofer et al [17] presented an approach for an integrated virtual process chain for SMC compression molding.…”
Section: Introductionmentioning
confidence: 99%